EKSPLORASI CERITA TAPA MALENGGANG SEBAGAI EKSPRESI GERAK TARI DAN CERMINAN KESADARAN LINGKUNGAN - Sholikha, Imroatu; Aisah, Nur; Nurkhoeriah, Siti; Puspitasari, Regita Eka; Salsabila, Nabila; Suci Sal Sabila, Sarifah; Nurmadani, Kurnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research explores Tapa Malenggang, a traditional dance from Muara Bulian, Jambi, which is not only rich in beautiful movements but also has a deep environmental message. This dance uses movements that tell the story of Tapa Malenggang, with dancers wearing brown cloth as a symbol of the Batang Hari River which is increasingly polluted. In this dance, the dancers' body movements symbolize people's concern about environmental degradation, especially river pollution which plays an important role in their lives. This research aims to analyze the application of the values contained in Tapa Malenggang through dance as a tool for cultural preservation and increasing environmental awareness. Using a qualitative approach with the Grounded Theory method with data sources namely interviews and document studies in the form of tapa malenggang dance and theater performances, and discussions with resource persons. This research aims to produce a theory about the relationship between Tapa Malenggang values, dance and environmental awareness. The research results show that every movement in Tapa Malenggang depicts the narrative, character and values contained in the Tapa Malenggang folklore through the expression of body movements, rhythm and symbolism in the dance. Every element in the Tapa Malenggang story, such as characters, plot and conflict, can be translated into dance movements that depict the journey of the main character, Mambang Diawan (Tapa Malenggang). By telling the story of the pollution of the Batang Hari River through the symbolism of brown cloth, this dance emphasizes the importance of preserving nature and invites people to care more about the environment. This research concludes that Tapa Malenggang is an artistic expression that combines cultural values and environmental awareness, and has an important role in building society's ecological awareness.